2018
DOI: 10.1093/jas/sky100
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for ewe reproductive performance and peri-parturient fecal egg counts and their genetic relationships with lamb body weights and fecal egg counts in Katahdin sheep

Abstract: This study estimated genetic parameters for ewe reproductive traits [number of lambs born (NLB) and weaned (NLW) per ewe lambing] and fecal egg counts (FEC) during the peri-parturient rise (PPR) for use in genetic evaluation of Katahdin sheep. Data included NLB and NLW for 23,060 lambings by 9,295 Katahdin ewes, 1,230 PPR at lambing (PPR0) for 750 ewes, 1,070 PPR at approximately 30 d postpartum (PPR30) for 611 ewes, BW at birth, weaning, and (or) post-weaning for 12,869 lambs, and FEC at weaning and (or) post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 26 publications
3
10
0
1
Order By: Relevance
“…We performed a supplementary analysis of the correlations between stage‐specific responses to infection, which further indicated that FEC was highly repeatable across stage‐specific infections (correlation between stages >0.5 in general; Appendix S2 and Table S7). Our results were thus globally consistent with the high genetic correlations observed between FEC measures at different ages in other sheep populations (Bishop & Stear, 2001; Brown & Fogarty, 2017; Goldberg et al, 2012; Notter et al, 2018; Pollott et al, 2004). Overall, there is little chance that periparturient limits to selection for parasite resistance stem from a lack of genetic variation at this stage (Bishop & Stear, 2001; Goldberg et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We performed a supplementary analysis of the correlations between stage‐specific responses to infection, which further indicated that FEC was highly repeatable across stage‐specific infections (correlation between stages >0.5 in general; Appendix S2 and Table S7). Our results were thus globally consistent with the high genetic correlations observed between FEC measures at different ages in other sheep populations (Bishop & Stear, 2001; Brown & Fogarty, 2017; Goldberg et al, 2012; Notter et al, 2018; Pollott et al, 2004). Overall, there is little chance that periparturient limits to selection for parasite resistance stem from a lack of genetic variation at this stage (Bishop & Stear, 2001; Goldberg et al, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…and Table S7). Our results were thus globally consistent with the high genetic correlations observed between FEC measures at different ages in other sheep populations Brown & Fogarty, 2017;Goldberg et al, 2012;Notter et al, 2018;Pollott et al, 2004). Overall, there is little chance that periparturient limits to selection for parasite resistance stem from a lack of genetic variation at this stage Goldberg et al, 2012).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Some mature Katahdin ewes have been shown to have GIN resistance traits similar to St Croix upon natural infection (Burke & Miller ). Recent work estimated the heritability ( h 2 ) of FEC in Katahdin lambs at 60 ( h 2 = 0.18–0.26) and 120 ( h 2 = 0.23–0.46) days of age (Ngere et al ), and periparturient ewes at lambing ( h 2 = 0.29–0.41) and 30 days postpartum ( h 2 = 0.17–0.31) (Notter et al ). These generally moderate heritabilities for FEC suggest that parasite resistance can be improved through genetic selection.…”
mentioning
confidence: 99%
“…Estimated breeding values for NLB as well as NLW in the current study were correlated with mean number of lambs born. The flock also had a higher value correlation between NLB and NLW, implying that there is low voluntary lamb removal (i.e., artificial rearing of lamb or fostering of lambs to other ewes) [13]. However, other EBVs, WWT,…”
Section: Discussionmentioning
confidence: 96%